Pengaruh Motivasi terhadap Keputusan Berkunjung Wisatawan ke Taman Panorama Baru Kota Bukittinggi - Suci Nurul Fadiya; Adek Kurnia Fiza (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find problems related to the motivation of tourists' visiting decisions. This type of research is quantitative descriptive using a causal associative approach with a survey method which aims to see the influence of motivation on the decision to visit. This research involved 90 respondents selected through purposive sampling. Data collection was carried out through a questionnaire distributed via Google Form using a Likert scale. The questionnaire was tested for validity and reliability. Data were analyzed using SPSS 20.00. The results of this research show that the motivation variable is in the good category, namely with an average value of 3.73, and the visiting decision variable shows the adequate category with an average value of 3.89. From the motivation value (X), the calculated F value is 120.175 with Sig 0.000 < 0.05, meaning that the motivation variable can explain the visiting decision variable significantly. Furthermore, an Adjusted R Square value of 0.577 was obtained, meaning that the influence of the motivation variable (X) on the visiting decision variable (Y) was 57.7%, while 42.3% was influenced by other factors.